Detection of Critical Situation of Longitudinal Vehicle Dynamics - Velayati, Widya Nila; Varrier, Sebastien (Institut Teknologi Sepuluh Nopember, 2014)
This research presents a method of detecting critical situation for longitudinal vehicle dynamics. First, the dynamical system is modeled that consists of longitudinal tire force and longitudinal aerodynamic drag force. The longitudinal tire force is well known to be highly nonlinear. However, one can classify it in three types of operation : normal zone, critical zone and skidding zone. Normal zone represents the linear part of longitudinal tire force while in the critical zone, the vehicle does no longer correspond to the linear system. The difference between the nonlinear force and its linear model is considered as a fault that has to be detected. The aim of this project is to detect that fault. As the system depends on the speed of the vehicle, a Linear Parameter Varying (LPV) dynamical system is considered and an LPV fault detection approach is handled. An extension of the parity-space approach for LPV systems is applied to detect the fault on the vehicle. In order to accommodate the existence of the faults, the Hâˆž robust control system has been designed. Afterward, it is found that the controller can accommodate the faults. This research have been also implemented on a 1/5th scale vehicle by the simulation.